Tunable Multimode Fiber Based Filter and Its Application in Cost-Effective Interrogation of Fiber-Optic Temperature Sensors - Li Wei; Anum Khattak; Connor Martz; Da-Peng Zhou (IEEE Photonics Journal, 2017)
We present a new tunable all-fiber compact multimode fiber (MMF)-based filter and its applications in fiber sensors. Using the matrix optics approach, we theoretically analyze the transmission characteristics of the tunable filter. The expression of the transmission of the optical filter is the same as that of a regular Mach–Zehnder interferometer (MZI) but with an additional optical phase shift in the sinusoidal function, which makes the MMF-based filter tunable. The phase shift could be changed by properly adjusting a polarization controller where the MMF is simply coiled into. The theoretical result has been verified by our experiment. The proposed tunable filter has been employed for intensity interrogation of a fiber Bragg grating (FBG)-based temperature sensor where the MMF-based filter serves as an edge filter. With the tuning technique, we are able to set the FBG peak to the linear regime of the interference pattern to achieve optimum sensing operation range. By monitoring the optical power changes, it is feasible to obtain information that permits temperature measurement with a simple and low-cost structure.